A Colonized People Persian hegemony, hybridity , and community identity in Ezra-Nehemiah - Janzen, David 1968- (2016)
The article draws on Achaemenid royal inscriptions in a postcolonial investigation of Ezra-Nehemiah’s portrayal of the community of immigrants from Babylon. The book presents the community’s identity as a hybrid of the way imperial hegemony portrays the colonized who live in the Persian Empire and of aspects of the community’s own Judean heritage that is strongly influenced by Yahwism. In Ezra 1–6, the community is portrayed as a group of colonists sent from the imperial center by the king, but, in these chapters, loyalty to the king amounts to loyalty to Yhwh, since it is the community’s God who commands the Persian king to act. In Ezra 7-Nehemiah 13, however, this loyal group of colonizers becomes a colonized people disloyal to their God and king. These chapters present the community as a group who has ceased to be the loyal imperial subjects of Ezra 1–6 and who have declined to the state of their ancestors, congenitally unable to keep Yahwistic and Persian law, and thereby justifying the colonized state of the community and imperial exploitation of its resources. In this section of the narrative, the community is just what Persian hegemony defines its colonized peoples to be: They are a group of “slaves” to the Persians, and rely utterly on individuals commissioned by the Persian king and sent from the center of the empire – that is, Ezra and Nehemiah – to lead them and to keep them loyal to their God and, therefore, a loyal colonized people to Persia.
Keywords: Ezra-Nehemiah -- postcolonialism -- Persian Empire -- Achaemenid inscriptions